EMDR and standard psychotherapy for paediatric cancer patients and their families: a pilot study - Zucchetti, Giulia; Ciappina, Sabrina; Roccia, Elvia; Concas, Deborah; Giordano, Mario; Battaglini, Chiara; Geuna, Tiziana; Peirolo, Claudia; Faretta, Elisa; Fernandez, Isabel; Quarello, Paola; Fagioli, Franca (Frontiers in Psychology, 2024)
Introduction This study examined the efficacy of eye movement desensitisation and reprocessing (EMDR) therapy compared with standard psychotherapy (SP) in treating post-traumatic stress disorder (PTSD) in paediatric oncology patients and their families in the early stage of cancer treatment. The secondary aim of this study was to assess whether EMDR therapy has a different impact on post-traumatic growth compared to SP. Methods Forty patients were randomly assigned to EMDR or SP groups. The Impact of Event Scale – Revised (IES-R) and the Distress Thermometer (DT) were used to assess PTSD symptoms at pre-treatment (at cancer diagnosis) and in the post-treatment stages (after 8 sessions). The Post-traumatic Growth Inventory-PTGI was administered in the post-treatment stage in order to evaluate positive changes. Results Both EMDR and SP are effective in reducing PTSD, but EMDR was significantly more effective than the SP in reducing scores on the IES-R, especially regarding the intrusive symptom subscale. Also, in the EMDR group there were higher scores of PTGI than in the standard group. Conclusion EMDR thus represents a promising treatment in the paediatric psycho-oncology setting.